Experimental study of boiling flow in a vertical heated annulus with local two-phase measurements and visualization. (July 2020) - Bottini, Joseph L.; Zhu, Longxiang; Ooi, Zhiee Jhia; Zhang, Taiyang; Brooks, Caleb S.
Highlights: Local two-phase data are collected in a 3-m-long boiling annulus channel. Local two-phase data separated by bubble group based on chord length. Point of Net Vapor Generation is identified visually. Flow structure is captured with a high-speed camera at five view ports. Abstract: Understanding the phenomena and predicting the behavior of two-phase flow are critical for safe design and operation of boiling systems. Local two-phase flow-boiling data were collected in an internally heated vertical annulus facility with a heated length of 3.0 m, an inner diameter of 19.05 mm, and an outer diameter of 38.10 mm. The data were collected with four-sensor probes which measure the void fraction, interfacial area concentration, and gas interface velocity at eleven radial locations over five axial locations within the boiling channel. In addition, the flow structure was captured with a high-speed camera at five viewports in between each of the instrumentation ports, and the Onset of Nucleate Boiling (ONB) and Point of Net Vapor Generation (PNVG) were identified for each of the conditions studied. The flow visualization shows the development of bubbly and slug flows within the channel which is accelerated for the low-pressure conditions. The local two-phase measurements show substantial void generation for the low-pressure conditions matched with an acceleration of the flow through the gas interface velocity. The interfacial area concentration is dominated by smaller group-1 bubbles and shows a decrease in total interfacial area concentration when larger group-2 bubbles dominate. This study provides detailed, accurate data for both the validation of multiphase computational fluid dynamics and system-analysis codes as well as the development of constitutive models in boiling flow.